Gotówkowa stopa wzrostu podtrzymywanego w analizie strategicznej wybranych przedsiębiorstw branży browarniczej - Słoński, Tomasz; Daszyńska-Żygadło, Karolina (Cash Sustainable Growth Rate in the Strategic Analysis of Chosen Brewery Companies., 2008)
The analysis of sustainable growth rate allows to improve considerably an assessment of SBU's strategic potential. The rate helps to compare the possible growth rate within the branch with the growth rate the firm's scheme to achieve. The article presents case studies from brewery sector. In those cases the V. Govindarajan and J. Shank's concept of sustainable growth rate was used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 507-517